Atmospheric Lunar Tide in the Low Latitude Thermosphere‐Ionosphere. Issue 11 (31st May 2022) - Lieberman, Ruth S.; Harding, Brian J.; Heelis, Roderick A.; Pedatella, Nicholas M.; Forbes, Jeffrey M.; Oberheide, Jens
Abstract: We present simultaneous, independent measurements of the atmospheric semidiurnal lunar tide in neutral winds and plasma velocities from NASA's Ionospheric Connection Explorer, and in atomic oxygen 135.6 nm airglow measured by the Global‐scale Observations of the Limb and Disk. Westward tidal winds near 115 km at the magnetic equator occur during part of the upward phase of the in‐situ plasma drift. Vertical motions associated with the field‐aligned plasma velocity occur away from the magnetic equator. The morphology of the lunar tide, and the phasing between the airglow and plasma velocities are consistent with E × B drift as a mechanism for linking neutral wind and plasma perturbations. This work provides the first observational quantification of global‐scale E‐ and F‐region coupling through E × B and field‐aligned vertical drifts. Plain Language Summary: Tidal winds propagating upward from the neutral atmosphere influence ionospheric dynamo electric fields and vertical plasma drifts. However, these mechanisms have never been fully identified in comprehensive and simultaneous measurements spanning the ionosphere‐thermosphere‐mesosphere (ITM) system. The atmospheric lunar tide is an effective marker of ITM coupling because it originates at Earth's surface, propagates vertically, and is fully sampled in daytime‐only and post‐sunset satellite measurements. We utilize measurements from two new NASA missions to track the lunar tide in neutral and plasma velocities, and in an electron density proxy. Our work provides observational confirmation, and quantitative estimates of F‐region vertical plasma motions driven by neutral winds and electrodynamical forces. Key Points: The semidiurnal lunar tide is identified in simultaneous, independent measurements of F‐region airglow, and neutral and plasma velocities Tidal patterns observed in airglow, plasma and neutral motions are consistent with both field‐aligned and E × B mechanisms of plasma uplift The semidiurnal lunar tide is an effective marker of atmosphere‐ionosphere coupling